Similarities and Differences between LaNiO_{2} and CaCuO_{2} and Implications for Superconductivity - A. S. Botana; M. R. Norman (Physical Review X, 2020)
The recent observation of superconductivity in hole-doped NdNiO_{2} has generated considerable attention. The similarities and differences between this infinite-layer nickelates and cuprates are still an open question. To address this issue we derive, via-principles calculations, essential facts related to the electronic structure and magnetism of RNiO_{2} (R=La, Nd) in comparison to their cuprate analog CaCuO_{2}. From this detailed comparison, we find that RNiO_{2} are promising as cuprate analogs. Besides the much larger d-p energy splitting, and the presence of R 5d states near the Fermi energy in the parent compound, all other electronic-structure parameters seem to be favorable in the context of superconductivity as inferred from the cuprates. In particular, the large value of the longer-range hopping t^{′} and the e_{g} energy splitting are similar to those obtained in cuprates. Doping further acts to increase the cupratelike character of these nickelates by suppressing the self-doping effect of the R 5d bands.